The Effect Of Current On SMAW Welding To Tensile Strength And Micro Structure Of Low Carbon Steel - Khafifudin M (International Conference on Engineering and Technology Development (ICETD), 2017)
This study aims to determine the effect of the welding current strength against the tensile strength and microstructure SMAW electrode E 6013. This study used low carbon steel. Material treated with a variation of welding current 65 amperes, 75 amperes and 85 amperes using reverse polarity DC SMAW with E7018 electrode diameter of 2.5 mm. DC reverse polarity that the electrode holder is connected to the positive pole and the metal stem is connected to the negative pole. This type of connection used is a blunt connection. Tensile testing specimens and micro photograph. The tensile strength of the weld joint highest among75 specimens Amper is equal to 319.44 N/but the tensile strength of raw materials was higherthan 75 amperes is equal to 490.97N/, group welding decreased by 171.53 N / under the influence of welding. According to the results of research can be concluded that with a strong variation of welding current structure changes as a result of cooling and therefore contributes to the strength of the material that is an increase of the rawmaterials